Pengembangan Sistem Informasi Transaksi Penjualan UMKM Menggunakan Metode Rapid Application Development - Arif, Naufal; Amalia; Misna Asqia (The Indonesian Journal of Computer Science, 2025)
The digital transformation has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt information systems to support their operational process. However, many existing applications do not fully address the specific needs of MSMEs. This study develops a web-based sales transaction information system using the Rapid Application Development (RAD) method. The system is designed with lightweight technologies, namely ExpressJS, EJS and SQLite, and employs the Model-View-Controller (MVC) architecture. Its core features include transaction recording, data management, automated data backup and payment monitoring. The system was evaluated through Alpha Testing conducted by the developers and Beta Testing involving end user. To ensure alignment with real world requirements, The system was implemented at Uwais Telur, a local egg distribution MSME, and documented in the form of a Software Requirements Spesification (SRS).